Modelling the impacts of urban upgrading on population dynamics. (April 2016) - Schwarz, Nina; Flacke, Johannes; Sliuzas, Richard
Abstract: Due to the rapid pace of urbanization, cities in the global South are growing with most of this growth occurring in informal settlements. Urban upgrading aims to improve living conditions in such settlements by improving the infrastructure but might lead to unexpected effects such as income segregation. InformalCity, a spatially explicit agent-based model, simulates the implications of urban upgrading in an artificial city. Our simulation experiments show that maintenance of the upgraded infrastructure, the scope of upgrading efforts, and timing (early vs. late investments) affect infrastructure quality, housing development and income segregation. However, we also find that urban upgrading interventions can have contradictory effects; for example, maintenance increases the quality of infrastructure and income segregation. Thus, policy makers need to establish clear targets for upgrading projects, and empirical evaluation studies should consider studying the impacts of urban upgrading on an entire city's development rather than limiting them to informal settlements. Highlights: We model urban upgrading of informal settlements in an agent-based model (ABM). ABM allows evaluating impacts of upgrading on living conditions in the whole city. City-wide evaluation is a significant improvement over traditional approaches. Five configuration parameters for urban upgrading were distinguished. Upgrading has contradictory effects on infrastructure quality and segregation.